Chemically modified carbon nanotubes (CNTs) for adsorption of mercury / Nuruzatulifah bt Asari @ Mansor - Asari @ Mansor, Nuruzatulifah (2013)
Functionalized multiwalled carbon nanotubes (MWCNTs) for the removal of mercury ion from aqueous solution were studied. This project had two parts, first part was the functionalization of MWCNTs using different method. Second, the performance study of the removal mercury ion using functionalized MWCNTs. Functionalization of MWCNTs was carried out using two separate methods. The first method was a gas phase treatment in a Universal Temperature Program (UTP) reactor by flowing H2SO4/SO3 vapour onto the MWCNTs. The second method was a liquid phase treatment which includes refluxing the MWCNTs in H2SO4. All samples were heated at different temperatures (100, 200, 300 oC) for 2 hours. Fourier Transform Infrared Spectroscopy (FTIR) analysis shows the presence of oxygen and sulphur containing groups such as C=O, –COOH, S=O, C–S and O–H in all samples. Microscopic characterization by High ResolutionTransmission Electron Microscopy (HRTEM) shows, there was some defective region on the outer wall and small amount of amorphous carbon impurities remained on carbon surfaces after purification process. Raman spectroscopy showed that the gas phase functionalized samples exhibits the highest D to G band intensity (ID/IG) ratio as compared to liquid phase functionalized samples. The liquid phase functionalized sample creates fewer defects than gas phase from the strong intensity of graphite peak observed from X-ray Diffraction (XRD) technique. All functionalized samples shows the mesopores surface characteristic where the gas phase functionalized samples exhibits the high mesopores size distribution. The optimum condition of treatment was found to be at 200 oC for both gas and liquid phase. The gas phase functionalized MWCNTs exhibit the excellent characteristic with the highest acidic functional groups, greatest specific surface area and highest mesopores size distribution. Langmuir and Freundlich Isotherm models were used to test the adsorption experiment data. The gas (B7) and liquid (B10) phase functionalized iv MWCNTs which treated at 200 oC, fits well the Langmuir Isotherm than pristine MWCNTs. The liquid phase adsorbent sample exhibit the highest maximum sorption capacity (qm) of 135.04 mg/g as compared to raw and gas phase functionalized MWCNTs samples.